Eksistensi Manusia dalam Filsafat Soren Kierkegaard - Armawi, Armaidy (Jurnal Filsafat "WISDOM", 2011)
indirectly with cultural issues. The problems also have touched values of human rights, such as: restlessness, isolation, etc. Modern-man increasingly is trapped by a hole which is dug by him(her)self. Technological advances in modern civilization have made man arrogant that eventually plunged the man into a visible-life problem. Those basic or fundamental problems are very urgent and demanding an answer. To give the answer, it is needed an approach which orientates to human existence. It can be found in thoughts of Sören Kierkegaard. Kierkegaard distinguishes the human existence into three distinctive levels, namely: (1) the aesthetic existence, (2) the ethics existence, (3) the religious existence. These levels will affect the human existence and it is its way. He differs from other existentialist philosophers who in general are atheists. Keywords: human existence, Sören Kierkegaard, cultural issues, the aesthetic existence, the ethics existence, the religious existence